Mutation of ataxia–telangiectasia mutated is associated with dysfunctional glutathione homeostasis in cerebellar astroglia. Issue 2 (15th October 2015) - Campbell, Andrew; Bushman, Jared; Munger, Joshua; Noble, Mark; Pröschel, Christoph; Mayer‐Pröschel, Margot
Abstract : Astroglial dysfunction plays an important role in neurodegenerative diseases otherwise attributed to neuronal loss of function. Here we focus on the role of astroglia in ataxia–telangiectasia (A–T), a disease caused by mutations in the ataxia–telangiectasia mutated ( ATM ) gene. A hallmark of A–T pathology is progressive loss of cerebellar neurons, but the mechanisms that impact neuronal survival are unclear. We now provide a possible mechanism by which A–T astroglia affect the survival of cerebellar neurons. As astroglial functions are difficult to study in an in vivo setting, particularly in the cerebellum where these cells are intertwined with the far more numerous neurons, we conducted in vitro coculture experiments that allow for the generation and pharmacological manipulation of purified cell populations. Our analyses revealed that cerebellar astroglia isolated from Atm mutant mice show decreased expression of the cystine/glutamate exchanger subunit xCT, glutathione (GSH) reductase, and glutathione‐S‐transferase. We also found decreased levels of intercellular and secreted GSH in A–T astroglia. Metabolic labeling ofl ‐cystine, the major precursor for GSH, revealed that a key component of the defect in A–T astroglia is an impaired ability to import this rate‐limiting precursor for the production of GSH. This impairment resulted in suboptimal extracellular GSH supply, which in turn impaired survival of cerebellar neurons. We show that by circumventing the xCT‐dependent import ofl ‐cystine through addition of N ‐acetyl‐l ‐cysteine (NAC) as an alternative cysteine source, we were able to restore GSH levels in A–T mutant astroglia providing a possible future avenue for targeted therapeutic intervention. GLIA 2016;64:227–239 Main Points: Our study of astroglia in Ataxia‐telangiectasia shows defective glutathione homoeostasis that indirectly contributes to neuronal death. Provision of exogenous cysteine overcomes the astroglia insufficiency and increases survival of mutant neurons.